Catalogues of bulge and fountain formation at Strokkur geyser in 2017, 2020 and 2022: Heights, rising speeds and seismic signal - Eibl, Eva P. S.; Karmacharya, Sandeep; Shevchenko, Alina V.; Walter, Thomas R.; Hersir, Gylfi Páll (GFZ Data Services, 2024)
Abstract Strokkur is a pool geyser in southwest Iceland that erupts every 3.7 minutes. Eruptions start with a blue water bulge that soon turns white (bulge phase) before the water bubble bursts into a jetting water fountain (jet phase). We measured the bulge rising velocity and height and fountain rising velocity and height using video cameras and drones from GFZ and the accompanying ground motion using seismometers from the University of Potsdam. We publish the derived products from video data and seismic data here.